2012
DOI: 10.3109/00016357.2012.734407
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological features and malignant transformation of oral lichen planus: A 12-years retrospective study

Abstract: At present, OLP is accepted as being a potential malignant disorder, therefore lifelong follow-up is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 32 publications
0
27
0
4
Order By: Relevance
“…122 Hemidesmosomes, together with the anchoring filaments, form 123 the hemidesmosomes anchoring filament complex, which plays an im- group of diseases and only a few describe the epidemiological features 156 of the whole spectrum of autoimmune diseases in particular population. 157 Studies from Eastern Europe show that pemphigus is the most common 158 autoimmune blistering disease with an estimated incidence and preva- 159 lence of 4 and 24.8 per 100 000 inhabitants, respectively [10]. Similar 160 results also emerged in studies conducted in Western Asia, East Asia 161 and Africa, where pemphigus was also found to be the most prevalent 162 autoimmune bullous dermatose [11][12][13].…”
mentioning
confidence: 56%
“…122 Hemidesmosomes, together with the anchoring filaments, form 123 the hemidesmosomes anchoring filament complex, which plays an im- group of diseases and only a few describe the epidemiological features 156 of the whole spectrum of autoimmune diseases in particular population. 157 Studies from Eastern Europe show that pemphigus is the most common 158 autoimmune blistering disease with an estimated incidence and preva- 159 lence of 4 and 24.8 per 100 000 inhabitants, respectively [10]. Similar 160 results also emerged in studies conducted in Western Asia, East Asia 161 and Africa, where pemphigus was also found to be the most prevalent 162 autoimmune bullous dermatose [11][12][13].…”
mentioning
confidence: 56%
“…Lichen planus (LP) is a chronic inflammatory disease of stratified squamous epithelia that affects 0.2–4% of the general population, with a predilection for women (63–67%) . Several genetic and environmental factors such as hepatitis C infection, hypertension, depression and rheumatologic disorders have been reported to be associated with LP .…”
Section: Introductionmentioning
confidence: 99%
“…Lichen planus (LP) is a chronic inflammatory disease of stratified squamous epithelia that affects 0.2-4% of the general population, with a predilection for women (63-67%). [1][2][3][4][5] Several genetic and environmental factors such as hepatitis C infection, hypertension, depression and rheumatologic disorders have been reported to be associated with LP. 1 Although recent data suggest a primary pathogenic role of autoreactive cytotoxic T cells inducing keratinocyte apoptosis, the triggering antigen and exact mechanisms involved remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…His lesions had clinical WHO criteria for OLP, and he also had typical lichen affection in nails (nail pterygium). Therefore patients diagnosed with OLP must be followed up, as well as those with OLR, especially in erosive, atrophic, bullous and keratotic forms, for early diagnosis of malignant transformation if that occurs (21). …”
Section: Discussionmentioning
confidence: 99%